The Role of Songbooks in the Preservation of Children’s Folk Songs in Kindergarten - Mihelač, Lorena (Revija za elementarno izobraževanje, 2022)
The paper presents an analysis of songbooks used in kindergarten. It outlines the need for renewal of the existing kindergarten curriculum from the perspective of preserving the Slovenian music tradition, and within this context, the indispensable role of children’s folk songs in the preservation of Slovenian folk music. Furthermore, it tackles the following three issues: (i) the disproportionate representation of children’s folk songs and author songs in songbooks; (ii) the information provided about children’s folk songs in songbooks, and (iii) the representation of children’s folk songs in kindergarten.
Keywords: children’s folk songs, preschool education, songbooks